Trends in the Singapore telecommunications industry : a discussion on the impact of liberalisation, globalisation and emerging technologies. - Chua, Kenneth Cheng Hao. (2008)
This paper discusses the future of the telecommunications industry in Singapore. The major factors affecting the Singapore telecommunications industry related to the trends of liberalisation, privatisation and globalisation.